Policy Simulation of Increasing Production and Income of Small Fisherman Household in Sidomulyo, Ngadirojo, Pacitan - Supriyadi Supriyadi; Anthon Efani (Faculty of Fisheries and Marine Science, Brawijaya University, 2020)
The objectives of this study were to identify characteristics of small fishermen household; model smallholder household economy based on production decisions, work-flow allocations, income, and consumption; simulate policy scenarios for increasing production and income of small fishermen household. The analytical method in this study uses the Two-stage Least Square (2SLS) method which is used to estimate the parameters of an equation with program SAS 9.1.3, while the simulation analysis is used to obtain policy alternatives that can increase the production and income of small fishermen. The result of the research average total production of beltfish is as much as 13,3 kg per month. The small fisherman households in the study area allocated the work time of their household members to the on-fishing activities at 36.4% and non-fishing at 63.6%. There is a relationship between production, work time, income, and consumption in the economic model of small fisherman households. The choice of policy to improve fishing technology can increase the production and income of small fishermen while the increase in fuel price will decrease the income of small fishermen households.